Simulation of direct injection, mixing and combustion of CNG fuel in a single - cylinder engine with different injector orientations using CFD - Mohd Azlan Fahmi, Muhammad Azmi; Mohd Fadzil, Abdul Rahim; Rizalman, Mamat (Institution of Engineering and Technology, 2022)
The direct injection system is widely used in the automotive industry, especially for performance enhancement and cleaner emissions. The study proposed a direct injection system in a small, single-cylinder compressed natural gas engine. However, its compactness provides a minimum space for direct injector installation. Therefore, a suitable injector orientation that meets space availability and is practically effective must be determined. The main objective is to determine the best injector orientation for the direct injection process using computational fluid dynamics by analysing the effect of top and side injection on the cylinder flow pattern, in-cylinder pressure and temperature. The analysis was performed by using Ansys Fluent. The dynamic mesh strategy is utilised to ensure a realistic solution of in-cylinder flow, gaseous injection, mixing and combustion. Based on the visualisation results, it is found that the injector orientation affects the overall injected mass of fuel by deteriorating the injection penetration, injection velocity and spray cone, as demonstrated by the top injection case. As a result, the methane mass fraction in the cylinder is reduced. The plotted results showed the side injection has a higher cold flow and combustion pressure and temperature with values of 112.38 bar and 3834.3 K, while the top injection has 98.99 bar and 2381.1 K. Even though the simulation overpredicted the pressure and temperature for both cases, because of inaccurate convective heat transfer solution, the resultant pressures and temperatures provide a valuable indication of how the injector orientation affects the overall direct injection of natural gas engine's performance. In the current study, the side injection performed better than the top injection. The side injection produced a higher pressure and temperature because the higher mass was transferred during the side injection. The study provided valuable insights into the ideal direct injection of compressed natural gas.